Faktor Penyebab Pekerja Tidak Paham Dana Pensiun, Pentingnya Edukasi dan Digitalisasi Industri Dana Pensiun di Indonesia - Yunus, Syarifudin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Many workers do not understand the importance of retirement funds. This research aims to describe data and information on workers' understanding in Jakarta about pension funds. The instruments used include questionnaires and content analysis. It can be concluded that 89% of workers do not have pension funds and only 11% of workers have pension funds. There are 80% of workers who do not rely on pension funds from their place of work, only 20% of workers hope to receive pension funds from their place of work. This condition can be caused by 1) ignorance about pension funds due to lack of education, 2) unavailability of funds to participate in pension funds, or 3) unavailability of access to purchase pension funds. There is the potential for pension funds to be developed targeting individual workers (not solely because of the company). To be able to increase participation in pension funds among workers, two important factors must be improved, namely 1) continuous education and 2) availability of digital access to have pension funds.